2014
DOI: 10.1021/am4057375
|View full text |Cite
|
Sign up to set email alerts
|

Printable Highly Catalytic Pt- and TCO-Free Counter Electrode for Dye-Sensitized Solar Cells

Abstract: Here we show that a counter electrode based on carbon network supported Cu2ZnSnS4 nanodots on Mo-coated soda-lime glass for dye-sensitized solar cells can outperform the conventional best electrode with Pt nanoparticles on the fluorine-doped SnO2 conducting glass. In the as-developed electrode, all of the elements are of high abundance ratios with low materials cost. The fabrication is scalable because it is conducted by a screen-printing based approach. Therefore, this research lays a solid ground for the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Therefore, it is very likely that the value of R ct would not influence the FF value to a large extent in our case, as supported by some literatures that there is no clear correlation between the values of FF and R ct . [50][51][52][53][54] In fact, some literatures reported that the FF value is influenced by the R ct value, i.e., the larger the R ct , the smaller the FF. [55][56][57][58][59][60] Since there are so many factors to influence the FF, our study suggests no obvious relationship between the values of FF and R ct , which is in good agreement with the previous literatures.…”
Section: Analysis Was Used To Estimate the Active Surface Areas (Amentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is very likely that the value of R ct would not influence the FF value to a large extent in our case, as supported by some literatures that there is no clear correlation between the values of FF and R ct . [50][51][52][53][54] In fact, some literatures reported that the FF value is influenced by the R ct value, i.e., the larger the R ct , the smaller the FF. [55][56][57][58][59][60] Since there are so many factors to influence the FF, our study suggests no obvious relationship between the values of FF and R ct , which is in good agreement with the previous literatures.…”
Section: Analysis Was Used To Estimate the Active Surface Areas (Amentioning
confidence: 99%
“…[55][56][57][58][59][60] Since there are so many factors to influence the FF, our study suggests no obvious relationship between the values of FF and R ct , which is in good agreement with the previous literatures. [50][51][52][53][54] This study reports on the preparation of Ti plates with TNT imprints and their applications on …”
Section: Analysis Was Used To Estimate the Active Surface Areas (Amentioning
confidence: 99%
“…Different electrodes have shown similar CV curves with two pairs of redox peaks (Ox-1/Red-1, Ox-2/Red-2) being observed. As the reaction of I − /I 3 − redox electrolyte in CEs is I 3 − + 2e − ↔ 3I − , so the reduction process is pertinent to the CEs performance and should be considered in our analysis 58 . Two important parameters for catalytic activity are the peak current ( i p ) and the peak-to-peak separation ( E pp ) 59 61 .…”
Section: Resultsmentioning
confidence: 99%
“…6b , the cathodic peak current density ( i pa ) and anodic peak current density ( i pc ) of CZTS-NS are 1.82 mA·cm −2 and 1.73 mA·cm −2 , higher than that of CZTS-SP ( i pa = 1.21 mA·cm −2 , i pc = 1.18 mA·cm −2 ), but slightly lower than that of Pt ( i pa = 2.14 mA·cm −2 , i pc = 2.15 mA·cm −2 ). The E pp in a pair is in an inverse correlation with the standard electrochemical rate constant of the corresponding redox reaction 58 . The lower E pp represents the higher kinetic ability for I 3 − reduction 57 .…”
Section: Resultsmentioning
confidence: 99%
“…To date, extensive attempts have been made to explore alternatives that do not involve Pt, such as conducting polymers, [6][7][8][9] carbonaceous materials, [10][11][12][13][14][15][16] and inorganic compounds. [17][18][19][20][21][22][23][24][25][26] Among the carbonaceous materials, graphene, possessing a single layer structure of two-dimensional graphite, has recently generated enormous amounts of research activity; this material is regarded as a good substitute for CE material because of its high specific surface area, excellent thermal and chemical properties, as well as exceptional electrical conductivity. [27] Moreover, the surface functionalization of graphene leads to the formation of defects or oxygen-containing functional groups located at its edge sites, which play a crucial role in providing active sites for I 3 À reduction.…”
Section: Introductionmentioning
confidence: 99%